Motivational Processes in the Physical Education Classroom: Proposal for an Inclusive Physical Education Didactic Unit - Solaguren-Beascoa Merino, Sandra; Romero da Cruz, Sheila (Journal of Learning Styles, 2021)
The present study has a twofold objective. Firstly, following the fundamental principles of the Self-Determination Theory, it presents an analysis of the motivational processes that occur in the Physical Education classroom; secondly, taking as support the educational approach of Motor Co-Opedagogy and the pedagogical models of Cooperative Learning and Personal and Social Responsibility, it sets out the design of an intervention proposal for an Inclusive Physical Education Didactic Unit. For data collection, the questionnaires adapted to the Spanish context of the Basic Psychological Needs Measurement Scale (BPNES) and the Perceived Locus of Causality in Physical Education Scale (PLOC Scale) were used with a sample of 30 students, aged between 16 and 17 years, enrolled in 1st year of high school. The results reveal the positive relationship between the satisfaction of Basic Psychological Needs (BPN) for learning and the adoption of more self-determined behaviours and the processes of identified, introjected and external regulation. Furthermore, the data associated higher levels of the three BPNs for learning in boys than in girls. Based on the results obtained, an intervention proposal for an Inclusive Physical Education Didactic Unit was designed.
Keywords: Physical Education; Inclusion; Motor Co-Opedagogy; Self-Determination Theory; Basic Psychological Needs.